Preferensi Pakan Beberapa Strain Kecoak Jerman, Blattella Germanica (Dictyoptera: Blattellidae) - Apriza Hongko Putra (Pendidikan Biologi STKIP YPM Bangko, 2018)
This study was conducted to determine kind of favorite food of some german cockroach strains, that were VCRU-WHO ( Susceptible strain), PLZ-PDG, GFA-JKT and KRSA-BDG. Some foods used in this research were pineapple, strawberry, peanut and chocolate jam. Observed data consisted of presence frequency and total consumed food for 96 hours observation. The result showed that highest presence frequency of VCRU-WHO, PLZ-PDG and KRSA-BDG was on pineapple jam, with average frequency were 17, 18.50 and 17.25 times, while in GFA-JKT was on strawberry jam (10.5 times). The highest food consumption level of VCRU-WHO, PLZ-PDG and KRSA-BDG was on pineapple jam with average weights were 128, 69 and 104 mg, while GFA JKT preferred to strawberry jam with average weight was 45.50 mg. There was different food preference between GFA JKT which preferred to strawberry jam and others which preferred to pineapple jam. Regression analysis resulted in an equation, y = 2.19 + 50.37 and R2 = 0,27 or r = 0,52, P< 0.05. This analysis showed that there is positive correlation between presence frequency and total food consumption but not significant.